PATHOGENIC VARIATION AMONG FUSARIUM OXYSPORUM F. SP. LYCOPERSICI ISOLATES AND VARIETAL SCREENING OF TOMATO AGAINST WILT UNDER SOUTH GUJARAT, INDIA - G. B. CHOPADA; PUSHPENDRA SINGH; CHANDULAL KORAT (The Bioscan, 2014)
Ten isolates of Fusarium oxysporum f. sp. lycopersici collected from different tomato growing areas of South Gujarat. Pathogenic variability study was carried out on six tomato varieties using root dip inoculation technique. All isolates showed variation in incubation period which was range from 18 days to 25 days. Wilt incidence in six test genotypes were ranged between 30 to 100 %. Isolates SGFOL-7, SGFOL-4 and SGFOL-8 proved highly virulent pathogen showed 72.78%, 63.89% and 61.11% mean wilt incidence on all varieties respectively. Rest of isolates showed moderately to less virulent reaction. Ten tomato varieties were screened for resistance to SGFOL-7 isolate in pot, varieties NS-2535, Heamsona and GT-2 were found moderately resistant with 33.33, 33.33 and 46.67 per cent wilt incidence respectively.